2021
DOI: 10.1093/heapol/czab140
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of long-lasting insecticidal net distribution through schools in Southern Tanzania

Abstract: Universal coverage with effective vector control remains the mainstay of malaria vector control in sub-Saharan Africa Tanzania has utilized a number of mechanisms for the maintenance of long-lasting insecticidal net (LLIN) coverage over time. Schools have been identified as one potential channel for continuous distribution of LLIN. This research aims to evaluate an annual school based LLIN distribution programme in Tanzania which began in 2013, called the School Net Programme (SNP). Following each of the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…These findings are supported by retrospective research in Tanzania that found that continuous distribution at quantities equal to population × 20–25% led to higher ITN access in household surveys than when quantified at lower levels (Koenker et al in review). School distribution in Tanzania has previously been demonstrated to maintain population ITN access and use in the absence of mass campaigns [ 4 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by retrospective research in Tanzania that found that continuous distribution at quantities equal to population × 20–25% led to higher ITN access in household surveys than when quantified at lower levels (Koenker et al in review). School distribution in Tanzania has previously been demonstrated to maintain population ITN access and use in the absence of mass campaigns [ 4 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strategies such as school-based interventions aiming to improve LLIN coverage and use in older children are gaining traction. In Tanzania, a study to evaluate a school-based LLIN distribution programme found that LLIN use increased from 57 to 77% among primary school children [ 38 ]. Targeting school-aged children, who can serve as agents of change, can also improve LLIN use within households [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…School distribution in Tanzania has previously been demonstrated to maintain population ITN access and use in the absence of mass campaigns [4,13].…”
Section: Discussionmentioning
confidence: 99%